High-power wide-aperture electron-beam-pumped lasers on dense gases - Abdullin E. N.; Ivanov S. N.; Kovalchuk B. M.; Losev V. F.; Mesyats G. A. Gennady Andreyevich; Skakun V. S.; Tarasenko V. F.; Turchanovsky I. Yu.; Yastremsky A. G. (2006, 2006)
В фонде НТБ ТПУ отсутствует